UTILIZING INTERACTIVE LEARNING MEDIA TO ENHANCE FOURTH GRADE STUDENTS’ UNDERSTANDING OF PLANT PARTS FUNCTIONS AT SD NEGERI 52 LUBUKLINGGAU - Intan Permata Kusuma (CV Grasta Glory, 2025)
This study aims to develop and test the effectiveness of interactive learning media in improving the learning outcomes of Grade IV students of SD Negeri 52 Lubuklinggau on science materials about the function of plant parts. The background of this research is based on students' low understanding of abstract scientific concepts and the limited learning media available in schools. Using a Research and Development (R&D) approach with the Borg and Gall development model, the interactive media was systematically designed and validated by experts. The validation results indicated that the media fell into the